The Effect of Temperature Differences on the TEG-Based Conversion of Thermal Energy into Electrical Energy - Lapananda, Nuraliva F.P; Arbie, Asri; Yunus, Muhammad; Latief, Muh. Fachrul; Kurniasari, Septiana; Meidji, Icha Untari (Journal of Science and Science Education, 2024)
Thermoelectric Generator (TEG) is an energy conversion device used as an electricity generator to create hot electric currents through temperature differences. This research aims to determine the effect of time on temperature differences from burning rice husks (Oryza sativa L.) in series and parallel configurations. This research method was carried out experimentally by burning rice husk biomass in a kiln and utilizing the heat of the fire to convert it into electrical energy. The TEG total of 48 TEG pieces which produce the highest current in the series configuration produces the highest with respective values ​​of current 0.09 A and voltage 1.02 V, and the parallel configuration TEG produces the highest with respective values ​​of current 0.98 A and voltage 0.25 V. The highest temperature difference reaches 30.5°C in the series configuration and 31.8°C in the parallel configuration. The longer the burning time, the more significant the resulting temperature difference. Likewise, the greater the electric current and voltage, the longer the burning time.